Method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid
By combining complex probiotics and lysine fermentation waste liquid, and using multi-stage treatment technology of organic-inorganic hybrid materials and temperature-controlled responsive materials, the problems of low lysine extraction efficiency and incomplete purification of waste liquid in the prior art are solved, and multi-stage purification of efficient lysine extraction and waste liquid are achieved, and nutrient-rich biological liquid fertilizer is prepared, reducing environmental pollution.
Patent Information
- Application Number
- CN202411761505.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to efficiently extract lysine, realize intelligent adsorption of specific components of waste liquid and remove harmful ions, and the materials cannot be reused, and it is impossible to thoroughly treat lysine fermentation waste liquid to efficiently convert it into environmentally friendly liquid biological fertilizer.
Combining the composite probiotics and lysine fermentation waste liquid, organic-inorganic hybrid materials are prepared through montmorillonite, polyvinyl alcohol and sodium alginate, and their efficient adsorption of lysine and impurities are used to enhance the adsorption capacity and purification effect through temperature-controlled responsive materials, achieving multi-stage treatment of waste liquid and efficient utilization of resources.
It improves the extraction efficiency of lysine, realizes efficient purification of waste liquid and reusable resources, prepares nutrient-rich biological liquid fertilizers, reduces environmental pollution, and conforms to the development concept of green and environmental protection.
Smart Images

Figure CN119751171A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fertilizer preparation, in particular to a method for preparing biological fertilizer by combining composite probiotics with lysine fermentation waste liquid. Background Art
[0002] With the rapid development of the global economy and the continuous growth of the population, the demand for fertilizers in agricultural production is increasing. At the same time, environmental protection has become a global focus. Under such a background, how to efficiently utilize resources, reduce environmental pollution, and develop green and environmentally friendly fertilizers has become an important issue in the agricultural field. Lysine, as an important amino acid, is widely used in feed, food, medicine and other fields. Lysine is usually produced by fermentation, which produces a large amount of waste liquid. These waste liquids contain underutilized lysine and other nutrients. If they are directly discharged, it will not only cause a waste of resources, but also cause serious pollution to the environment. Therefore, it is of great practical significance to effectively treat and utilize the lysine fermentation waste liquid. The existing technology has certain technical defects. First, the existing technology lacks materials for efficiently extracting lysine and cannot specifically adsorb lysine and impurities in the waste liquid. Second, the existing technology is difficult to achieve intelligent adsorption of specific components of the waste liquid and removal of harmful ions, and the materials cannot be reused. Furthermore, the existing technology does not thoroughly treat lysine fermentation waste liquid and cannot efficiently convert it into environmentally friendly liquid bio-fertilizer. For this reason, we propose a method for preparing bio-fertilizer by combining composite probiotics with lysine fermentation waste liquid. Summary of the invention
[0003] The object of the present invention is to provide a method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid.
[0004] In order to solve the problems raised in the above background technology, the present invention provides the following technical solution: a method for preparing a biofertilizer by combining composite probiotics with lysine fermentation waste liquid, wherein the method for preparing the biofertilizer specifically comprises the following steps: Step 1: Collect lysine fermentation waste liquid, filter it through a filter with a pore size of 100 μm, and control the filtration pressure at 0.2 MPa. Then, add polyaluminium chloride flocculant to the waste liquid for stirring reaction to make the suspended particles condense and precipitate. Then, remove the precipitated impurities through a filter with a pore size of 100 μm again to ensure that the waste liquid has no obvious impurities and pollutants. Step 2: montmorillonite is selected as an adsorption carrier and the montmorillonite is treated. The montmorillonite is first ground and filtered, and then the ground montmorillonite is immersed in a hydrochloric acid solution and stirred for reaction to remove impurities in the montmorillonite. After standing for a period of time, the montmorillonite is rinsed with deionized water to neutrality, and then dried and calcined. The high-temperature calcination changes the crystal structure of the montmorillonite, increases its porosity, and thus increases the surface area and active sites; Step 3, preparing an organic-inorganic hybrid material, selecting polyvinyl alcohol as an organic polymer material and sodium alginate as a bioactive molecule for preparing an organic-inorganic hybrid material, selecting poly (N-isopropylacrylamide) as a polymer with temperature responsiveness, ferroferric oxide nanoparticles as magnetic nanoparticles and a strongly acidic styrene-based cation exchange resin for preparing a temperature-controlled responsive material, and mixing the treated montmorillonite, polyvinyl alcohol and sodium alginate to prepare an organic-inorganic hybrid material, first dissolving polyvinyl alcohol in distilled water to form a solution, then adding the treated montmorillonite thereto for stirring and reacting, so that the montmorillonite is evenly dispersed in the polyvinyl alcohol, and after the reaction is completed, adding a sodium alginate solution to the mixed solution for a cross-linking reaction to obtain an organic-inorganic hybrid material; Step 4: adding the prepared organic-inorganic hybrid material to the lysine fermentation waste liquid for stirring reaction. During the stirring process, the montmorillonite in the organic-inorganic hybrid material has a large surface area and abundant active sites due to the treatment, and can effectively adsorb lysine and impurities in the waste liquid. As the stirring continues, the hybrid material is fully in contact with the waste liquid, and the lysine molecules are gradually adsorbed onto the surface and pores of the hybrid material. The stirring is continued for a period of time to ensure that the hybrid material fully adsorbs the lysine and impurities in the waste liquid. After the stirring reaction is completed, the hybrid material is filtered and separated to obtain a lysine-rich material and a preliminarily treated waste liquid; Step 5, using ferrous chloride and ferric chloride to synthesize ferroferric oxide nanoparticles, and then dissolving N-isopropylacrylamide monomer, ammonium persulfate initiator and N,N'-methylenebisacrylamide crosslinker in a mixed solvent of ethanol and water to carry out polymerization reaction, and after the reaction, mixing the synthesized poly N-isopropylacrylamide solution with the ferroferric oxide nanoparticles, and after mixing, uniformly dispersing and stirring under the action of ultrasound, so that the poly N-isopropylacrylamide is wrapped on the surface of the ferroferric oxide nanoparticles to form magnetic composite particles with temperature responsiveness; Step 6: Combine the magnetic composite particles with a strongly acidic styrene-based cation exchange resin to obtain a temperature-controlled responsive material, add the temperature-controlled responsive material to the preliminarily treated waste liquid for stirring reaction, and utilize temperature responsiveness to enhance the adsorption capacity of unreacted lysine precursor substances and small molecule organic acids in the waste liquid. At the same time, the ion exchange resin selectively adsorbs heavy metal ions such as lead ions, cadmium ions, mercury ions and other harmful ions in the waste liquid. After the reaction is completed, a permanent magnet with an external magnetic field is used to recover the temperature-controlled responsive material close to the treated waste liquid. Since the ferrosoferric oxide nanoparticles are magnetic, the temperature-controlled responsive material will be attracted to the vicinity of the permanent magnet under the action of the magnetic field, thereby achieving separation and recovery to obtain further purified waste liquid. Step 7: The extracted lysine and the further purified waste liquid are placed in a reaction container and mixed. After mixing, the composite probiotics are added for fermentation reaction. Under this condition, the composite probiotics begin to actively grow and metabolize. The probiotics convert lysine and other nutrients in the waste liquid into organic matter that is easily absorbed by plants through biochemical reactions, and produce a variety of beneficial metabolites, including organic acids and biological enzymes. The mixed liquid is stirred regularly during the reaction to ensure that the probiotics are evenly distributed and fully act on the mixed liquid to obtain a biological liquid fertilizer.
[0005] As a further solution of the present invention: in the step 1, the amount of polyaluminium chloride flocculant added is 8g-10g per liter of waste liquid, and after adding, it is stirred at a speed of 130r / min-150r / min for 20min-30min to make it evenly mixed, and then allowed to stand for 1h-2h.
[0006] As a further scheme of the present invention: In the step 2, the specific process of treating montmorillonite is as follows: first, the montmorillonite is ground and filtered to pass through a 100-mesh sieve, and then the ground montmorillonite is immersed in a hydrochloric acid solution with a concentration of 4%-6%, and stirred at a temperature of 38°C-42°C and a speed of 90r / min-110r / min for 1.5h-2.5h to remove impurities in the montmorillonite, and then the montmorillonite is rinsed with deionized water to neutrality, and then dried at 75°C-85°C, and the dried montmorillonite is placed in a muffle furnace and calcined at 380°C-420°C for 2.5h-3.5h.
[0007] As a further scheme of the present invention: In the step three, the specific process for preparing the organic-inorganic hybrid material is as follows: polyvinyl alcohol is dissolved in distilled water at 75°C-85°C and stirred evenly to form a solution with a concentration of 9%-11%, and then the treated montmorillonite is added thereto, and stirred at a speed of 190r / min-210r / min for 2.5h-3.5h at 48°C-52°C to uniformly disperse the montmorillonite in the polyvinyl alcohol, and then a 4%-6% sodium alginate solution is added at a speed of 4r / min-6r / min, and a cross-linking reaction is carried out at a temperature of 38°C-42°C for a reaction time of 1.5h-2.5h, wherein the mass ratio of montmorillonite, polyvinyl alcohol and sodium alginate is 1:2-3:0.2-0.4.
[0008] As a further scheme of the present invention: in the step 4, the mass ratio of the organic-inorganic hybrid material to the lysine fermentation waste liquid is 5:9-11, and the stirring reaction is carried out at a temperature of 28°C-32°C, at a speed of 110r / min-130r / min, and the stirring time is 3.5h-4.5h.
[0009] As a further scheme of the present invention: in the step 5, the process for synthesizing ferrosoferric oxide nanoparticles is as follows: ferrous chloride and ferric chloride are dissolved in deionized water at a molar ratio of 1:1.5-2.5, and under the protection of nitrogen, ammonia water is slowly added dropwise, and the reaction is carried out at 60°C-70°C for 2h-3h to form ferrosoferric oxide nanoparticles, which are then centrifuged and washed with deionized water and ethanol to obtain pure ferrosoferric oxide nanoparticles.
[0010] As a further scheme of the present invention: in the step 5, the mass ratio of N-isopropylacrylamide monomer: ammonium persulfate initiator: N,N'-methylenebisacrylamide crosslinker is 100:1-2:0.5-1.5, the volume ratio of ethanol and water in the mixed solvent of ethanol and water is 1:1, the polymerization temperature is 68°C-72°C, the polymerization time is controlled to be 3h-4h, and the poly N-isopropylacrylamide solution and the ferrosoferric oxide nanoparticles are mixed and ultrasonically dispersed and stirred at 40°C-50°C for 2h-3h.
[0011] As a further scheme of the present invention: in the step six, the magnetic composite particles and the strongly acidic styrene-based cation exchange resin are combined in a mass ratio of 1:1-2, the temperature-controlled responsive material is added to the waste liquid after preliminary treatment, the mass ratio of the temperature-controlled responsive material to the waste liquid is 1:7-9, and the reaction is stirred at 43°C-47°C at a speed of 90r / min-110r / min for 2.5h-3.5h. After the reaction is completed, the external magnetic field strength is 0.5T-1.5T.
[0012] As a further scheme of the present invention: in the step seven, the mass ratio of the added lysine, waste liquid and composite probiotics is 1:9-11:0.45-0.55, the reaction system is controlled at a constant temperature of 34°C-36°C, the pH value in the container is maintained at 6.8-7.2, the fermentation reaction lasts for 46h-50h, the mixed solution is stirred regularly during the reaction, the stirring speed is controlled to 80r / min-100r / min, the stirring time is 10min-15min each time, and the stirring is performed once every 2h-3h.
[0013] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are: 1. The present invention prepares an organic-inorganic hybrid material by using montmorillonite, polyvinyl alcohol and sodium alginate. After fine treatment and calcination, the montmorillonite has a rich pore structure and high active sites, and can efficiently adsorb impurities such as unreacted raw materials and pigments in lysine fermentation waste liquid. The adsorption principle is that the layered structure of montmorillonite and the increased surface area and active sites after treatment can bind these impurities in the waste liquid by physical adsorption and chemical adsorption. For the adsorption of lysine, the ion exchange effect on the surface of montmorillonite and the affinity generated by the specific structure formed with polyvinyl alcohol and sodium alginate are mainly used to selectively adsorb lysine in the lysine fermentation waste liquid. Polyvinyl alcohol plays a role of bonding and stabilizing the structure, so that the montmorillonite is evenly dispersed. Sodium alginate gives the material biological activity and promotes the cross-linking reaction to form a stable structure. In the process of extracting lysine, the hybrid material specifically adsorbs the target substance, improves the lysine extraction efficiency, provides a high-concentration lysine raw material for the subsequent preparation of liquid biological fertilizer, and improves the nutritional value of the fertilizer; 2. The present invention forms an intelligent responsive material by using poly N-isopropylacrylamide, ferroferric oxide nanoparticles and a strongly acidic styrene-based cation exchange resin. The poly N-isopropylacrylamide is temperature-sensitive. When the temperature is lower than its lower critical solution temperature, the polymer is hydrophilic and stretches in water. When the temperature rises to above its lower critical solution temperature, the polymer changes from hydrophilic to hydrophobic, undergoes a phase change, and the molecular chains shrink and aggregate. In the process of treating waste liquid, when the temperature rises to a suitable range, the poly N-isopropylacrylamide undergoes a phase change, which enhances the reaction of unreacted lysine precursors in the waste liquid. The adsorption capacity of specific components such as bulk substances and small molecular organic acids is mainly through hydrophobic interaction and intermolecular van der Waals force to adsorb these specific components on the shrinking polymer surface. The ferroferric oxide nanoparticles give the material magnetism, which is convenient for separation and recovery through an external magnetic field, so as to achieve material reuse and reduce costs. The strong acid styrene-based cation exchange resin selectively adsorbs harmful components of heavy metal ions in the waste liquid, further purifies the waste liquid, and the treated waste liquid is mixed with the extracted lysine for probiotic fermentation, which can improve the safety and quality of liquid biofertilizer. 3. The present invention first performs multi-stage treatment on the lysine fermentation waste liquid. After collecting the waste liquid, a filter is used for preliminary filtration to remove large particle impurities, then a flocculant is added and stirred and allowed to stand to allow fine suspended particles to condense and precipitate, and the waste liquid is filtered again to ensure that there are no obvious impurities in the waste liquid. This operation effectively removes large particle impurities and fine suspended particles in the waste liquid, laying a good foundation for subsequent treatment. During the composite probiotic fermentation process, the probiotics convert the extracted lysine and the nutrients in the purified waste liquid into organic matter that is easily absorbed by plants, and at the same time produce a variety of beneficial metabolites, including organic acids, biological enzymes, etc. These metabolites can improve soil structure, increase soil permeability and water retention, improve soil fertility, and promote the growth and development of plant roots. In addition, the entire preparation process realizes the efficient utilization of lysine fermentation waste liquid, reduces the pollution of waste liquid to the environment, conforms to the development concept of green environmental protection, and provides new ways and methods for sustainable agricultural development. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A schematic diagram of the method steps in an embodiment of the present invention; Figure 2 It is a schematic diagram for comparing performance parameters of embodiments of the present invention. DETAILED DESCRIPTION
[0015] The specific embodiments of the present invention will be further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.
[0016] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0017] Please see attached Figure 1 -Attached Figure 2 The present invention provides a method for preparing a biofertilizer by combining composite probiotics with lysine fermentation waste liquid. The method for preparing the biofertilizer specifically comprises the following steps: Step 1: Collect lysine fermentation waste liquid, filter it through a filter with a pore size of 100 μm, and control the filtration pressure at 0.2 MPa. Then, add polyaluminium chloride flocculant to the waste liquid for stirring reaction to make the suspended particles condense and precipitate. Then, remove the precipitated impurities through a filter with a pore size of 100 μm again to ensure that the waste liquid has no obvious impurities and pollutants. Step 2: montmorillonite is selected as an adsorption carrier and the montmorillonite is treated. The montmorillonite is first ground and filtered, and then the ground montmorillonite is immersed in a hydrochloric acid solution and stirred for reaction to remove impurities in the montmorillonite. After standing for a period of time, the montmorillonite is rinsed with deionized water to neutrality, and then dried and calcined. The high-temperature calcination changes the crystal structure of the montmorillonite, increases its porosity, and thus increases the surface area and active sites; Step 3, preparing an organic-inorganic hybrid material, selecting polyvinyl alcohol as an organic polymer material and sodium alginate as a bioactive molecule for preparing an organic-inorganic hybrid material, selecting poly (N-isopropylacrylamide) as a polymer with temperature responsiveness, ferroferric oxide nanoparticles as magnetic nanoparticles and a strongly acidic styrene-based cation exchange resin for preparing a temperature-controlled responsive material, and mixing the treated montmorillonite, polyvinyl alcohol and sodium alginate to prepare an organic-inorganic hybrid material, first dissolving polyvinyl alcohol in distilled water to form a solution, then adding the treated montmorillonite thereto for stirring and reacting, so that the montmorillonite is evenly dispersed in the polyvinyl alcohol, and after the reaction is completed, adding a sodium alginate solution to the mixed solution for a cross-linking reaction to obtain an organic-inorganic hybrid material; Step 4: adding the prepared organic-inorganic hybrid material to the lysine fermentation waste liquid for stirring reaction. During the stirring process, the montmorillonite in the organic-inorganic hybrid material has a large surface area and abundant active sites due to the treatment, and can effectively adsorb lysine and impurities in the waste liquid. As the stirring continues, the hybrid material is fully in contact with the waste liquid, and the lysine molecules are gradually adsorbed onto the surface and pores of the hybrid material. The stirring is continued for a period of time to ensure that the hybrid material fully adsorbs the lysine and impurities in the waste liquid. After the stirring reaction is completed, the hybrid material is filtered and separated to obtain a lysine-rich material and a preliminarily treated waste liquid; Step 5, using ferrous chloride and ferric chloride to synthesize ferroferric oxide nanoparticles, and then dissolving N-isopropylacrylamide monomer, ammonium persulfate initiator and N,N'-methylenebisacrylamide crosslinker in a mixed solvent of ethanol and water to carry out polymerization reaction, and after the reaction, mixing the synthesized poly N-isopropylacrylamide solution with the ferroferric oxide nanoparticles, and after mixing, uniformly dispersing and stirring under the action of ultrasound, so that the poly N-isopropylacrylamide is wrapped on the surface of the ferroferric oxide nanoparticles to form magnetic composite particles with temperature responsiveness; Step 6: Combine the magnetic composite particles with a strongly acidic styrene-based cation exchange resin to obtain a temperature-controlled responsive material, add the temperature-controlled responsive material to the preliminarily treated waste liquid for stirring reaction, and utilize temperature responsiveness to enhance the adsorption capacity of unreacted lysine precursor substances and small molecule organic acids in the waste liquid. At the same time, the ion exchange resin selectively adsorbs heavy metal ions such as lead ions, cadmium ions, mercury ions and other harmful ions in the waste liquid. After the reaction is completed, a permanent magnet with an external magnetic field is used to recover the temperature-controlled responsive material close to the treated waste liquid. Since the ferrosoferric oxide nanoparticles are magnetic, the temperature-controlled responsive material will be attracted to the vicinity of the permanent magnet under the action of the magnetic field, thereby achieving separation and recovery to obtain further purified waste liquid. Step 7: The extracted lysine and the further purified waste liquid are placed in a reaction container and mixed. After mixing, the composite probiotics are added for fermentation reaction. Under this condition, the composite probiotics begin to actively grow and metabolize. The probiotics convert lysine and other nutrients in the waste liquid into organic matter that is easily absorbed by plants through biochemical reactions, and produce a variety of beneficial metabolites, including organic acids and biological enzymes. The mixed liquid is stirred regularly during the reaction to ensure that the probiotics are evenly distributed and fully act on the mixed liquid to obtain a biological liquid fertilizer.
[0018] In one embodiment of the present invention: in step 1, the amount of polyaluminium chloride flocculant added is 8g-10g per liter of waste liquid. After adding, the mixture is stirred at a speed of 130r / min-150r / min for 20min-30min to be evenly mixed, and then allowed to stand for 1h-2h.
[0019] In one embodiment of the present invention: in step 2, the specific process of treating montmorillonite is as follows: first, the montmorillonite is ground and filtered to pass through a 100-mesh sieve, and then the ground montmorillonite is immersed in a hydrochloric acid solution with a concentration of 4%-6%, and stirred at a temperature of 38°C-42°C at a speed of 90r / min-110r / min for 1.5h-2.5h to remove impurities in the montmorillonite, and then the montmorillonite is rinsed with deionized water to neutrality, and then dried at 75°C-85°C, and the dried montmorillonite is placed in a muffle furnace and calcined at 380°C-420°C for 2.5h-3.5h.
[0020] In one embodiment of the present invention: In step three, the specific process for preparing the organic-inorganic hybrid material is as follows: polyvinyl alcohol is dissolved in distilled water at 75°C-85°C and stirred evenly to form a solution with a concentration of 9%-11%, and then the treated montmorillonite is added thereto, and stirred at a speed of 190r / min-210r / min at 48°C-52°C for 2.5h-3.5h to make the montmorillonite evenly dispersed in the polyvinyl alcohol, and then 4%-6% sodium alginate solution is added at a speed of 4r / min-6r / min, and a cross-linking reaction is carried out at a temperature of 38°C-42°C for 1.5h-2.5h, wherein the mass ratio of montmorillonite, polyvinyl alcohol and sodium alginate is 1:2-3:0.2-0.4.
[0021] In one embodiment of the present invention: in step 4, the mass ratio of the organic-inorganic hybrid material to the lysine fermentation waste liquid is 5:9-11, and the stirring reaction is carried out at a temperature of 28°C-32°C, at a speed of 110r / min-130r / min, and the stirring time is 3.5h-4.5h.
[0022] In one embodiment of the present invention: in step five, the process for synthesizing ferrosoferric oxide nanoparticles is as follows: ferrous chloride and ferric chloride are dissolved in deionized water at a molar ratio of 1:1.5-2.5, and under nitrogen protection, ammonia water is slowly added dropwise, and the mixture is reacted at 60°C-70°C for 2h-3h to form ferrosoferric oxide nanoparticles, which are then centrifuged and washed with deionized water and ethanol to obtain pure ferrosoferric oxide nanoparticles.
[0023] In one embodiment of the present invention: in step 5, the mass ratio of N-isopropylacrylamide monomer: ammonium persulfate initiator: N,N'-methylenebisacrylamide crosslinker is 100:1-2:0.5-1.5, the volume ratio of ethanol to water in the mixed solvent of ethanol and water is 1:1, the polymerization temperature is 68°C-72°C, the polymerization time is controlled to be 3h-4h, and the poly N-isopropylacrylamide solution and the ferrosoferric oxide nanoparticles are ultrasonically dispersed and stirred at 40°C-50°C for 2h-3h.
[0024] In one embodiment of the present invention: in step six, the magnetic composite particles and the strongly acidic styrene-based cation exchange resin are combined in a mass ratio of 1:1-2, the temperature-controlled responsive material is added to the waste liquid after preliminary treatment, the mass ratio of the temperature-controlled responsive material to the waste liquid is 1:7-9, and the reaction is stirred at 43°C-47°C at a speed of 90r / min-110r / min for 2.5h-3.5h. After the reaction is completed, the external magnetic field strength is 0.5T-1.5T.
[0025] In one embodiment of the present invention: in step seven, the mass ratio of the added lysine, waste liquid and composite probiotics is 1:9-11:0.45-0.55, the reaction system is controlled at a constant temperature of 34°C-36°C, the pH value in the container is maintained at 6.8-7.2, the fermentation reaction lasts for 46h-50h, the mixed solution is stirred regularly during the reaction, the stirring speed is controlled to 80r / min-100r / min, the stirring time is 10min-15min each time, and the stirring is performed once every 2h-3h.
[0026] In one embodiment of the present invention: in step 1, when adding polyaluminium chloride flocculant to the waste liquid for stirring reaction, ultrasonic treatment is applied at the same time, with an ultrasonic frequency of 20kHz-30kHz and a power of 80W-120W to further promote the coagulation and precipitation of suspended particles, thereby improving the filtration effect and impurity removal rate.
[0027] In one embodiment of the present invention: in step 4, when the prepared organic-inorganic hybrid material is added to the lysine fermentation waste liquid for stirring reaction, nitrogen is introduced into the system with a nitrogen flow rate of 0.5L / min-1.5L / min to prevent lysine from being oxidized during the stirring process, thereby ensuring the extraction efficiency and purity of lysine, and also helping to reduce the oxidative effects that the hybrid material may be subjected to during the stirring process, thereby improving its stability and service life.
[0028] In one embodiment of the present invention: in step 2, after the montmorillonite is dried and before calcination, the montmorillonite is immersed in a 2%-4% hydrogen peroxide solution for 0.5 hour to 1 hour to further remove organic impurities in the montmorillonite, improve the adsorption performance and active sites of the montmorillonite, and provide a better basis for the subsequent preparation of organic-inorganic hybrid materials.
[0029] Example 1, please refer to the attached Figure 1 -Attached Figure 2First, the lysine fermentation waste liquid was collected, and then the lysine fermentation waste liquid was filtered through a filter with a pore size of 100 μm, and the filtration pressure was controlled at 0.2 MPa. Then, 10 g of polyaluminum chloride flocculant per liter was added to the waste liquid, and it was stirred at a speed of 150 r / min for 30 minutes to make it evenly mixed, and then it was allowed to stand for 2 hours, and the precipitated impurities were removed again through a filter with a pore size of 100 μm. Then, the montmorillonite was treated, the montmorillonite was ground and passed through a 120-mesh sieve, and then immersed in a 6% hydrochloric acid solution, and stirred at a speed of 110 r / min at 42°C for 2.5 hours to remove impurities, and then rinsed with deionized water until neutral, and then at 85 ℃, and then placed in a muffle furnace and calcined at 420℃ for 3.5h. Subsequently, an organic-inorganic hybrid material was prepared, polyvinyl alcohol was dissolved in 85℃ distilled water and stirred evenly to form a solution with a concentration of 11%, the treated montmorillonite was added, and stirred at 52℃ at a speed of 210r / min for 3.5h to make the montmorillonite evenly dispersed, and then a 6% sodium alginate solution was added at a speed of 6r / min, and a cross-linking reaction was carried out at 42℃ for 2.5h, wherein the mass ratio of montmorillonite, polyvinyl alcohol and sodium alginate was 1:3:0.4. The prepared organic-inorganic hybrid material was added to the lysine fermentation wastewater at a mass ratio of 5:11, and stirred at 32℃ at 130 The mixture was stirred at a speed of r / min for 4.5 h, and the hybrid material was separated by filtration to obtain a lysine-rich material and a preliminarily treated waste liquid. Ferroferric oxide nanoparticles were synthesized. Ferrous chloride and ferric chloride were dissolved in deionized water at a molar ratio of 1:2.5. Ammonia water was slowly added dropwise under nitrogen protection. The mixture was reacted at 70°C for 3 h to form ferroferric oxide nanoparticles. The particles were separated by centrifugation and washed with deionized water and ethanol. N-isopropylacrylamide monomer, ammonium persulfate initiator and N,N'-methylenebisacrylamide crosslinker were dissolved in a mixed solvent of ethanol and water in a volume ratio of 1:1 at a mass ratio of 100:2:1.5, and polymerization was carried out at 72°C for 4 h. h, the synthesized poly (N-isopropylacrylamide) solution was mixed with ferroferric oxide nanoparticles, and uniformly dispersed under ultrasonic action, and then stirred at 50°C for 3h to wrap the poly (N-isopropylacrylamide) on the surface of ferroferric oxide nanoparticles to form temperature-responsive magnetic composite particles, and the magnetic composite particles were combined with a strong acid styrene-based cation exchange resin at a mass ratio of 1:2 to obtain a temperature-controlled responsive material, and the temperature-controlled responsive material was added to the waste liquid after preliminary treatment, and the mass ratio of the temperature-controlled responsive material to the waste liquid was 1:9, and the reaction was stirred at 47°C at a speed of 110r / min for 3.5h. After the reaction was completed, an external magnetic field with an intensity of 1.A 5T permanent magnet was placed close to the treated waste liquid to recover the temperature-controlled responsive material, and further purified waste liquid was obtained. Finally, the extracted lysine and the further purified waste liquid were placed in a reaction container and mixed, and composite probiotics were added. The mass ratio of lysine, waste liquid and composite probiotics was 1:11:0.55. The reaction system was controlled at a constant temperature of 36°C, and the pH value in the container was maintained at 7.2. The fermentation reaction lasted for 50 hours, during which the mixed liquid was stirred regularly at a stirring speed of 100 r / min, each stirring time was 15 minutes, and stirring was performed every 3 hours to obtain a biological liquid fertilizer.
[0030] Example 2, please refer to the attached Figure 1 -Attached Figure 2First, the lysine fermentation waste liquid was collected, and then the lysine fermentation waste liquid was filtered through a filter with a pore size of 100 μm, and the filtration pressure was controlled at 0.2 MPa. Then, 8 g of polyaluminum chloride flocculant per liter was added to the waste liquid, and it was stirred at a speed of 130 r / min for 20 minutes to make it evenly mixed, and then it was allowed to stand for 1 hour, and the precipitated impurities were removed again through a filter with a pore size of 100 μm. Then, the montmorillonite was treated, the montmorillonite was ground and passed through a 100-mesh sieve, and then immersed in a 4% hydrochloric acid solution, and the reaction was stirred at a speed of 90 r / min at 38°C for 1.5 hours to remove impurities, and after being rinsed with deionized water to neutrality, it was heated at 75 ℃, and then placed in a muffle furnace and calcined at 380 ℃ for 2.5h. Subsequently, an organic-inorganic hybrid material was prepared, polyvinyl alcohol was dissolved in 75 ℃ distilled water and stirred evenly to form a solution with a concentration of 9%, the treated montmorillonite was added, and stirred at 48 ℃ at a speed of 190r / min for 2.5h to make the montmorillonite evenly dispersed, and then a 4% sodium alginate solution was added at a speed of 4r / min, and a cross-linking reaction was carried out at 38 ℃ for 1.5h, wherein the mass ratio of montmorillonite, polyvinyl alcohol and sodium alginate was 1:2:0.2. The prepared organic-inorganic hybrid material was added to the lysine fermentation waste liquid at a mass ratio of 5:9, and stirred at 28 ℃ at 110r / min. / min stirring for 3.5h, filtering and separating the hybrid material to obtain the lysine-rich material and the preliminarily treated waste liquid, synthesizing ferrosoferric oxide nanoparticles, dissolving ferrous chloride and ferric chloride in deionized water at a molar ratio of 1:1.5, slowly adding ammonia water under nitrogen protection, reacting at 60°C for 2h to form ferrosoferric oxide nanoparticles, centrifuging and washing with deionized water and ethanol, dissolving N-isopropylacrylamide monomer, ammonium persulfate initiator and N,N'-methylenebisacrylamide crosslinker in a mixed solvent of ethanol and water in a volume ratio of 1:1 at a mass ratio of 100:1:0.5, and carrying out polymerization at 68°C for 3h. h, the synthesized poly N-isopropylacrylamide solution was mixed with ferroferric oxide nanoparticles, and uniformly dispersed under ultrasonic action, and then stirred at 40°C for 2h to wrap the poly N-isopropylacrylamide on the surface of ferroferric oxide nanoparticles to form temperature-responsive magnetic composite particles, and the magnetic composite particles were combined with a strong acid styrene-based cation exchange resin at a mass ratio of 1:1 to obtain a temperature-controlled responsive material, and the temperature-controlled responsive material was added to the waste liquid after preliminary treatment, and the mass ratio of the temperature-controlled responsive material to the waste liquid was 1:7, and the reaction was stirred at 43°C at a speed of 90r / min for 2.5h. After the reaction was completed, an external magnetic field with an intensity of 0.A 5T permanent magnet was placed close to the treated waste liquid to recover the temperature-controlled responsive material, and further purified waste liquid was obtained. Finally, the extracted lysine and the further purified waste liquid were placed in a reaction container and mixed, and composite probiotics were added. The mass ratio of lysine, waste liquid and composite probiotics was 1:9:0.45. The reaction system was controlled at a constant temperature of 34°C, and the pH value in the container was maintained at 6.8. The fermentation reaction lasted for 46 hours, and the mixed liquid was stirred regularly during the period. The stirring speed was 80r / min, the stirring time was 10min each time, and the stirring was once every 2 hours to obtain a biological liquid fertilizer.
[0031] Example 3, please refer to the attached Figure 1 -Attached Figure 2First, the lysine fermentation waste liquid was collected, and then the lysine fermentation waste liquid was filtered through a filter with a pore size of 100 μm, and the filtration pressure was controlled at 0.2 MPa. Then, 10 g of polyaluminum chloride flocculant per liter was added to the waste liquid, and it was stirred at a speed of 150 r / min for 30 minutes to make it evenly mixed, and then it was allowed to stand for 2 hours, and the precipitated impurities were removed again through a filter with a pore size of 100 μm. Then, the montmorillonite was treated, the montmorillonite was ground and passed through a 100-mesh sieve, and then immersed in a hydrochloric acid solution with a concentration of 5%, and the reaction was stirred at a speed of 100 r / min at 40°C for 2 hours. h to remove impurities, rinse with deionized water to neutrality, dry at 80 ° C, and then place in a muffle furnace for calcination at 400 ° C for 3 h. Then prepare the organic-inorganic hybrid material, dissolve polyacrylamide in 80 ° C distilled water and stir evenly to form a solution with a concentration of 10%, add the treated montmorillonite, stir at 50 ° C at a speed of 200 r / min for 3 h to make the montmorillonite evenly dispersed, then add 5% sodium alginate solution at a speed of 5 r / min, and carry out cross-linking reaction at 40 ° C for 2 h, wherein the mass ratio of montmorillonite, polyacrylamide and sodium alginate is 1:2.5:0.3, The prepared organic-inorganic hybrid material was added to the lysine fermentation waste liquid at a mass ratio of 5:11, and stirred at 32°C at a speed of 130r / min for 4.5h. The hybrid material was separated by filtration to obtain a lysine-rich material and a preliminarily treated waste liquid. Ferroferric oxide nanoparticles were synthesized. Ferrous chloride and ferric chloride were dissolved in deionized water at a molar ratio of 1:2. Under nitrogen protection, ammonia water was slowly added dropwise, and the mixture was reacted at 65°C for 2.5h to form ferroferric oxide nanoparticles. The particles were separated by centrifugation and washed with deionized water and ethanol. N-isopropylacrylamide monomer and potassium persulfate initiator were added. The crosslinking agent N,N'-methylenebisacrylamide was dissolved in a mixed solvent of ethanol and water in a volume ratio of 1:1 at a mass ratio of 100:1.5:1, and the polymerization reaction was carried out at 70°C for 3.5 hours. The synthesized poly N-isopropylacrylamide solution was mixed with ferroferric oxide nanoparticles, and the mixture was uniformly dispersed under ultrasonic action. Then, the mixture was stirred at 45°C for 2.5 hours to wrap the poly N-isopropylacrylamide on the surface of ferroferric oxide nanoparticles to form magnetic composite particles with temperature responsiveness. The magnetic composite particles were mixed with weakly acidic styrene cation exchange resin in a mass ratio of 1:1.5, a temperature-controlled responsive material was obtained, the temperature-controlled responsive material was added to the waste liquid after preliminary treatment, the mass ratio of the temperature-controlled responsive material to the waste liquid was 1:9, the reaction was stirred at 45°C at a speed of 100r / min for 3h, after the reaction was completed, a permanent magnet with an external magnetic field strength of 1T was used to approach the treated waste liquid to recover the temperature-controlled responsive material, and further purified waste liquid was obtained. Finally, the extracted lysine and the further purified waste liquid were placed in a reaction container and mixed, and composite probiotics were added. The mass ratio of lysine, waste liquid and composite probiotics was 1:11:0.55. The reaction system was controlled at a constant temperature of 36°C, and the pH value in the container was maintained at 7.2. The fermentation reaction lasted for 50h, during which the mixed liquid was stirred regularly at a stirring speed of 100r / min, and each stirring time was 15min. The mixture was stirred once every 3h to obtain a biological liquid fertilizer. .
[0032] Design of the experiment: Experimental materials: three batches of waste liquid from the same source of lysine fermentation waste liquid, polyvinyl alcohol, montmorillonite (100 mesh), montmorillonite (120 mesh), 5% hydrochloric acid solution, 6% hydrochloric acid solution, sodium alginate, polyaluminium chloride flocculant, ferrous chloride, ferric chloride, ammonia water, N-isopropylacrylamide monomer, ammonium persulfate initiator, N,N'-methylenebisacrylamide cross-linking agent, ethanol, weak acid styrene cation exchange resin, strong acid styrene cation exchange resin, and composite probiotics; Experimental equipment: filter device, stirrer, muffle furnace, centrifuge, pH meter, electronic balance, constant temperature incubator and other equipment; Select three batches of waste liquid from the same source of lysine fermentation waste liquid, plant seeds of the same variety, and select a number of pakchoi seeds; Experimental steps: Three batches of lysine fermentation waste liquid were treated according to the methods of Examples 1, 2 and 3, and three groups were prepared for each example to ensure that the operation of each example was strictly carried out in accordance with the requirements, and various parameters during the operation were recorded. The average value of the three groups of experimental data for each example was taken; Lysine extraction efficiency determination: Sampling the solution after the waste liquid is adsorbed by the organic-inorganic hybrid material in each example, and determining the content of residual lysine in the solution by high performance liquid chromatography; Calculate the extraction efficiency of lysine: extraction efficiency = (lysine content in the initial waste liquid - lysine content in the solution after adsorption) / lysine content in the initial waste liquid × 100%; Determination of waste liquid purification degree: The waste liquid after treatment in each embodiment is tested to analyze the content of heavy metal ions (such as lead ions, cadmium ions, and mercury ions) therein; The heavy metal ion content was determined by atomic absorption spectrometry; Determination of nutrient content of biological fertilizer: The biological liquid fertilizer prepared in each embodiment was analyzed to determine the organic matter content and nitrogen content therein; The organic matter content was determined by potassium dichromate volumetric method, and the nitrogen content was determined by chemical analysis method; Plant growth determination: Sowing Chinese cabbage seeds respectively in the soils to which the biofertilizers of different embodiments were applied; Regularly observe and record the growth height and number of leaves of Chinese cabbage.
[0033] As attached Figure 2 As shown, through the analysis of the experimental data, it can be seen that Example 1 shows the best effect in terms of lysine extraction efficiency, waste liquid purification degree, biological fertilizer nutrient content and promotion of Chinese cabbage growth. Specifically, it is shown as follows: The lysine extraction efficiency is the highest, indicating that the organic-inorganic hybrid material of Example 1 has the strongest adsorption capacity for lysine; The content of heavy metal ions in the waste liquid is the lowest, indicating that the temperature-controlled responsive material of Example 1 has the best purification effect on the waste liquid; The organic matter and nitrogen contents in the biological fertilizer are the highest, indicating that the biological liquid fertilizer prepared in Example 1 is rich in nutrients and is beneficial to the growth of Chinese cabbage; From the growth of Chinese cabbage, the Chinese cabbage treated in Example 1 grew taller and had more leaves, which further proved the advantage of Example 1 in the process of combining composite probiotics with lysine fermentation waste liquid to prepare biofertilizer.
[0034] Although the present invention is disclosed as above in terms of preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, any modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid, characterized in that: The method for preparing the biofertilizer specifically comprises the following steps: Step 1: Collect lysine fermentation waste liquid, filter it through a filter with a pore size of 100 μm, and control the filtration pressure at 0.2 MPa. Then, add polyaluminium chloride flocculant to the waste liquid for stirring reaction to make the suspended particles condense and precipitate, and remove the precipitated impurities through a filter with a pore size of 100 μm again; Step 2: Select montmorillonite as an adsorption carrier and process the montmorillonite. First, grind and filter the montmorillonite, then soak the ground montmorillonite in a hydrochloric acid solution and stir to react. After the reaction is completed, stand for a period of time and then rinse the montmorillonite with deionized water until it is neutral, then dry and calcine it. Step 3, preparing an organic-inorganic hybrid material, selecting polyvinyl alcohol as an organic polymer material and sodium alginate as a bioactive molecule for preparing an organic-inorganic hybrid material, selecting poly (N-isopropylacrylamide) as a polymer with temperature responsiveness, ferroferric oxide nanoparticles as magnetic nanoparticles and a strongly acidic styrene-based cation exchange resin for preparing a temperature-controlled responsive material, and mixing the treated montmorillonite, polyvinyl alcohol and sodium alginate to prepare an organic-inorganic hybrid material, first dissolving polyvinyl alcohol in distilled water to form a solution, then adding the treated montmorillonite thereto for stirring and reacting, and after the reaction is completed, adding a sodium alginate solution to the mixed solution for a cross-linking reaction to obtain an organic-inorganic hybrid material; Step 4: adding the prepared organic-inorganic hybrid material to the lysine fermentation waste liquid for stirring reaction, and after the stirring reaction is completed, filtering and separating the hybrid material to obtain a lysine-rich material and a preliminarily treated waste liquid; Step 5, using ferrous chloride and ferric chloride to synthesize ferroferric oxide nanoparticles, and then dissolving N-isopropylacrylamide monomer, ammonium persulfate initiator and N,N'-methylenebisacrylamide crosslinker in a mixed solvent of ethanol and water to carry out polymerization reaction, and after the reaction, mixing the synthesized poly N-isopropylacrylamide solution with the ferroferric oxide nanoparticles, and after mixing, uniformly dispersing and stirring under the action of ultrasound, so that the poly N-isopropylacrylamide is wrapped on the surface of the ferroferric oxide nanoparticles to form magnetic composite particles with temperature responsiveness; Step 6: combining the magnetic composite particles with a strongly acidic styrene-based cation exchange resin to obtain a temperature-controlled responsive material, adding the temperature-controlled responsive material to the preliminarily treated waste liquid for stirring reaction, and after the reaction is completed, using a permanent magnet with an external magnetic field to approach the treated waste liquid to recover the temperature-controlled responsive material to obtain further purified waste liquid; Step 7: The extracted lysine and the further purified waste liquid are placed in a reaction container and mixed, and after mixing, the composite probiotics are added to carry out a fermentation reaction, and the mixed liquid is regularly stirred during the reaction to obtain a biological liquid fertilizer.
2. The method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid according to claim 1, characterized in that: In the step 1, the amount of polyaluminium chloride flocculant added is 8g-10g per liter of waste liquid. After adding, the mixture is stirred at a speed of 130r / min-150r / min for 20min-30min to be evenly mixed, and then allowed to stand for 1h-2h.
3. The method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid according to claim 1, characterized in that: In the step 2, the specific process of treating montmorillonite is as follows: first grind and filter the montmorillonite to pass through a 100-mesh sieve, then soak the ground montmorillonite in a 4%-6% hydrochloric acid solution, stir and react at a temperature of 38°C-42°C at a speed of 90r / min-110r / min for 1.5h-2.5h, then rinse the montmorillonite with deionized water until it is neutral, then dry it at 75°C-85°C, place the dried montmorillonite in a muffle furnace, and calcine it at 380°C-420°C for 2.5h-3.5h.
4. The method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid according to claim 1, characterized in that: In the step three, the specific process for preparing the organic-inorganic hybrid material is as follows: polyvinyl alcohol is dissolved in distilled water at 75°C-85°C and stirred evenly to form a solution with a concentration of 9%-11%, and then the treated montmorillonite is added thereto, and stirred at a speed of 190r / min-210r / min at 48°C-52°C for 2.5h-3.5h, and then a 4%-6% sodium alginate solution is added at a speed of 4r / min-6r / min, and a cross-linking reaction is carried out at a temperature of 38°C-42°C for 1.5h-2.5h, wherein the mass ratio of montmorillonite, polyvinyl alcohol and sodium alginate is 1:2-3:0.2-0.
4.
5. The method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid according to claim 1, characterized in that: In the step 4, the mass ratio of the organic-inorganic hybrid material to the lysine fermentation waste liquid is 5:9-11, and the stirring reaction is carried out at a temperature of 28°C-32°C, at a speed of 110r / min-130r / min, and the stirring time is 3.5h-4.5h.
6. The method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid according to claim 1, characterized in that: In the step 5, the process for synthesizing ferrosoferric oxide nanoparticles is as follows: ferrous chloride and ferric chloride are dissolved in deionized water at a molar ratio of 1:1.5-2.5, and under the protection of nitrogen, ammonia water is slowly added dropwise, and the mixture is reacted at 60°C-70°C for 2h-3h to form ferrosoferric oxide nanoparticles, which are then centrifuged and washed with deionized water and ethanol to obtain pure ferrosoferric oxide nanoparticles.
7. The method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid according to claim 1, characterized in that: In the step 5, the mass ratio of N-isopropylacrylamide monomer: ammonium persulfate initiator: N,N'-methylenebisacrylamide crosslinker is 100:1-2:0.5-1.5, the volume ratio of ethanol to water in the mixed solvent of ethanol and water is 1:1, the polymerization temperature is 68°C-72°C, the polymerization time is controlled to be 3h-4h, and the poly N-isopropylacrylamide solution and the ferrosoferric oxide nanoparticles are mixed and ultrasonically dispersed and stirred at 40°C-50°C for 2h-3h.
8. The method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid according to claim 1, characterized in that: In the step six, the magnetic composite particles and the strongly acidic styrene-based cation exchange resin are combined in a mass ratio of 1:1-2, the temperature-controlled responsive material is added to the waste liquid after preliminary treatment, the mass ratio of the temperature-controlled responsive material to the waste liquid is 1:7-9, and the reaction is stirred at 43°C-47°C at a speed of 90r / min-110r / min for 2.5h-3.5h. After the reaction is completed, the external magnetic field strength is 0.5T-1.5T.
9. The method for preparing biofertilizer by combining composite probiotics with lysine fermentation waste liquid according to claim 1, characterized in that: In the step seven, the mass ratio of the added lysine, waste liquid and composite probiotics is 1:9-11:0.45-0.55, the reaction system is controlled to be in a constant temperature environment of 34°C-36°C, the pH value in the container is maintained at 6.8-7.2, the fermentation reaction lasts for 46h-50h, the mixed solution is stirred regularly during the reaction, the stirring speed is controlled to 80r / min-100r / min, the stirring time is 10min-15min each time, and the stirring is performed once every 2h-3h.